Eksploracja danych z wykorzystaniem pakietu SPHINX - Smoląg, Klaudia; Jędrzejczyk, Waldemar (Data Mining with the Use of SPHINX Packet, 2005)
In this paper attention was paid to the process of processing data into knowledge. One of the stage of this process is Data Mining. In this paper the main property of chosen techniques of Data Mining (for example decision trees and neural networks) was shown. The idea of using these techniques was presented on the grounds of analysis of the problem of telework carrying out. The program Sphinx was used.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1081, s. 388-396